The Effects of Acute and Repeated Administration of Ketamine on Memory, Behavior, and Plasma Corticosterone Levels in Female Mice. (21st February 2023) - Acevedo, Jonathan; Mugarura, Naomi E.; Welter, Alex L.; Johnson, Emily M.; Siegel, Jessica A.
Highlights: Acute ketamine exposure increases anxiety-like behavior in adult female mice. Repeated ketamine exposure impaired novel object memory in adult female mice. Neither acute nor repeated ketamine exposure altered depression-like behavior in adult female mice. Neither acute nor repeated ketamine exposure altered plasma corticosterone levels in adult female mice. Abstract: Ketamine is an anesthetic drug that has recently been approved for the treatment of treatment-resistant depression. Females are diagnosed with Major Depressive Disorder at higher rates than males, yet most of the pre-clinical research on ketamine has been conducted in male subjects. Additionally, the literature on the acute and long-term behavioral and cognitive effects of ketamine shows conflicting results. It is important to examine the acute and long-term cognitive and behavioral effects of ketamine exposure at lower sub-anesthetic doses, as the recreational use of the drug at higher doses is associated with cognitive and memory impairments. The current study examined the effects of acute and repeated ketamine exposure on anxiety-like behavior, novel object recognition memory, depression-like behavior, and plasma corticosterone levels in 20 adult female C57BL/6J mice. Mice were exposed acutely or repeatedly for 10 consecutive days to saline or 15 mg/kg ketamine and behavior was measured in the open field test, novel object recognition test, and the Porsolt forced swim test. Plasma corticosterone levels were measured following behavioral testing. Acute ketamine exposure decreased locomotor activity and increased anxiety-like behavior in the open field test compared to controls, while repeated ketamine exposure impaired memory in the novel object recognition test. There were no effects of acute or repeated ketamine exposure on depression-like behavior in the Porsolt forced swim test or on plasma corticosterone levels. These findings suggest that a subanesthetic dose of ketamine alters behavior and cognition in female mice and the effects are dependent on the duration of exposure.